(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Metal-dielectric nanocomposite optical materials based on colloidal crystals have been prepared by electro-thermo-diffusion or magnetron sputtering of silver. Optical properties of these photonic crystals have been studied by angle-resolved reflectance and transmission spectroscopy. The interpretation of observed spectra has been made taking into account the Bragg diffraction, Fano resonance, Fabry-Perot resonance and surface plasmon-polaritons, which excitations contribute to the optical properties of plasmonic-photonic crystals.